Changes in Total Factor Productivity - Mariusz Prochniak (Poland. Competitiveness Report 2016. The Role of Economic Policy and Institutions, 2016)
The chapter includes the analysis of total factor productivity (TFP) for 11 CEE countries, referred to as the EU11 (Poland, Bulgaria, Croatia, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Romania, Slovakia, and Slovenia) during the 2006–2015 period. To assess changes in total factor productivity during that period, we also present the average TFP growth rates for the following subperiods: 2006–2007, 2008–2010, 2011–2014, and 2015. The analysis is conducted using the growth accounting framework. Growth accounting is an empirical exercise aimed at calculating how much economic growth is caused by changes in measurable factor inputs and in the level of technology.
Keywords: E24; O47; O52; 330; economic growth; total factor productivity; growth accounting